2022
DOI: 10.1093/femsec/fiac137
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial gut microbiomes of aculeate brood parasites overlap with their aculeate hosts’, but have higher diversity and specialization

Abstract: Despite growing interest in gut microbiomes of aculeate Hymenoptera, research so far focused on social bees, wasps and ants, whereas non-social taxa and their brood parasites have not received much attention. Brood parasitism however allows to distinguish between microbiome components horizontally transmitted by spill-over from the host with such inherited through vertical transmission by mothers. Here, we studied the bacterial gut microbiome of adults in seven aculeate species in four brood parasite-host syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…Berasategui et al (2016 18 ) showed that the microbiomes of several distinct species feeding on the same food source (conifer seedlings) were highly similar, suggesting that the environment played a bigger role in determining the gut microbial community. Similar results were found in beetles 19 and among army ants and their associated beetle species 20 , for which foraging habits and habitat structured the microbial communities and even brood parasites 21 . However, a large portion of the early evidence documenting environmental effects on the gut microbiome has been correlative.…”
Section: Introductionsupporting
confidence: 75%
“…Berasategui et al (2016 18 ) showed that the microbiomes of several distinct species feeding on the same food source (conifer seedlings) were highly similar, suggesting that the environment played a bigger role in determining the gut microbial community. Similar results were found in beetles 19 and among army ants and their associated beetle species 20 , for which foraging habits and habitat structured the microbial communities and even brood parasites 21 . However, a large portion of the early evidence documenting environmental effects on the gut microbiome has been correlative.…”
Section: Introductionsupporting
confidence: 75%
“…In particular, the bacterial community occurring in aquatic habitats plays a significant role in shaping the gut microbiota [ 23 ]. Hence, the environment, rather than genetics, shapes the gut microbiota of mosquitoes, as in many other insects that acquire their gut microbiota from the environment [ 24 , 25 ]. Such water-derived microbiota makes crucial the implementation of adequate larval diets in mass-rearing programs.…”
Section: Introductionmentioning
confidence: 99%
“…), morphological and physiological diversity across avian clades (Kohl, 2012). Brood parasitism models (Ronchetti et al., 2022) simplify some of these complexities and can be a valuable tool for parsing apart genetic and environmental factors and how they influence the community membership and structure of the wild avian microbiome. Further, the nested nature of host–microbe interactions within systems of parasitism present a complex set of challenges and opportunities for understanding factors that influence microbial composition and parasite success (Dheilly et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Brood parasitism models (Ronchetti et al, 2022) simplify some of these complexities and can be a valuable tool for parsing apart genetic and environmental factors and how they influence the community membership and structure of the wild avian microbiome.…”
Section: Mycobacteriummentioning
confidence: 99%